Molecular pathology and genetics of congenital hepatorenal fibrocystic syndromes. Issue 5 (1st May 2003) - Johnson, C A; Gissen, P; Sergi, C
Abstract : The hepatorenal fibrocystic (HRFC) syndromes are a heterogeneous group of severe monogenic conditions that may be detected before birth. Commonly, HRFC syndromes present in the neonatal and paediatric age, with consistent developmental abnormalities mostly involving the liver and kidney. The changes include the proliferation and dilatation of epithelial ducts in these tissues with abnormal deposition of extracellular matrix. In this review, we examine the clinical features and differential diagnoses of this group of syndromes, including autosomal recessive polycystic kidney disease (ARPKD), juvenile nephronophthisis (NPHP), Meckel-Gruber syndrome (MKS), Bardet-Biedl syndrome (BBS), and Jeune asphyxiating thoracic dystrophy (JATD). Extrahepatic manifestations include mostly bone and central nervous system abnormalities, dysmorphic features, and developmental delay. Previously, it has been suggested that ARPKD, JATD, and Ellis-van Creveld syndrome (EvC) may arise from defects in differentiation in a common developmental pathway. We review recent molecular advances in the recessive HRFC syndromes and discuss this hypothesis.